2014
DOI: 10.1063/1.4876961
|View full text |Cite
|
Sign up to set email alerts
|

Seismic metamaterials based on isochronous mechanical oscillators

Abstract: This Letter introduces a seismic metamaterial (SM) composed by a chain of mass-in-mass system able to filter the S-waves of an earthquake. We included the effect of the SM into the mono dimensional model for the soil response analysis. The SM modifies the soil behavior and in presence of an internal damping the amplitude of the soil amplification function is reduced also in a region near the resonance frequency. This SM can be realized by a continuous structure with inside a 3d-matrix of isochronous oscillator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
71
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(71 citation statements)
references
References 22 publications
0
71
0
Order By: Relevance
“…Shi et al (2014) propose a periodic foundation made up of concrete layers intermixed with rubber blocks, resulting in band gaps as low as 2.5 Hz, with the outcomes experimentally supported in Yan et al (2014) and Xiang et al (2012). Finocchio et al (2014) follow a different approach via composition of a seismic metamaterial from isochronous spherical oscillators rolling over a cycloidal trajectory. Shi (2013a, 2013b) integrate the periodic theory in the design of two-dimensional (2D) pile barriers and succeed in filtering out plane waves.…”
Section: Introductionmentioning
confidence: 99%
“…Shi et al (2014) propose a periodic foundation made up of concrete layers intermixed with rubber blocks, resulting in band gaps as low as 2.5 Hz, with the outcomes experimentally supported in Yan et al (2014) and Xiang et al (2012). Finocchio et al (2014) follow a different approach via composition of a seismic metamaterial from isochronous spherical oscillators rolling over a cycloidal trajectory. Shi (2013a, 2013b) integrate the periodic theory in the design of two-dimensional (2D) pile barriers and succeed in filtering out plane waves.…”
Section: Introductionmentioning
confidence: 99%
“…16 Finocchio et al introduced a seismic metamaterial composed of a chain of mass-in-mass system, which is able to filter the S-waves of an earthquake. 17 Aravantinos-Zafiris et al 18 reported results for a new layer-by-layer structure, which was studied as a candidate for pentamode behavior and other interesting elastic metamaterial properties. The structure had a simple cubic symmetry with connecting silicon rods, and it was an easy to fabricate structure.…”
Section: Introductionmentioning
confidence: 99%
“…The high frequency threshold of the gap is associated to the optical mode, obtained for γα = 0. It may be proven that, for the undamped case, the frequency band of the gap resides in the following interval (Finocchio et al, 2014;Huang et al, 2009) …”
Section: D Infinite Chainmentioning
confidence: 99%